(untitled) (Comprehensive Journal of Science, 2026)
The study aims to investigate and identify indicators of microbial and chemical contamination in drinking water from desalination and household purification stations in the city of Zintan.A totai of 11 random samples were collected from different parts of the city. Biological analyses showed that all samples were free of aerobic and coliform bacteria. This can be attributed to the distance of water sources supplying the purification stations from various pollution sources, as well as the use of modem purification devices for sterilization and the regular replacement of filters and membranes. Furthermore, all samples were found to be within the permissible chemical limits according to Libyan and international standards. Based on these results, the study recommends the need for periodic monitoring of drinking water, careful selection of purification stations, and raising consumer awareness of the necessity of the water safety procedures.